Ingredients for creating and sustaining growth for the long term - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
It is easy to explain why organisations need and want to grow. This applies not only to bottom line-oriented companies, but also non-profit entities. Just like the same way business management skills can and should be applied to public sector and not-for-profit set-ups, these organisations do seek growth too. However, while it is easy to engineer short spurts of growth one way or another, what differentiates a successful organisation from one less so, is whether this organisation can sustain growth over the long-term and achieve continuous success.